تطوير منهج تعليم اللغة العربية - Izzudin Musthafa (Jurnal Pendidikan Islam, 2012)
This study is based on the reality that learning process of Arabic in UIN Sunan Gunung DjatiBandung has not been able to reach the expected result. It is indicated in the result of languageproficiency test of the students who learn Arabic in a number of departments and programs in UINSGD Bandung. Therefore, it is necessary that appropriate model of curriculum be found as asolution to improve the quality of the graduates in mastery Arabic skills; that is, the curriculum forteaching learning Arabic that facilitates students to achieve the goals, content standard, teachinglearning process, and evaluation system. This study utilizes Research and Development method,since it focuses on curriculum development of Arabic in UIN SGD Bandung.